Pengaruh Negatif Change Order terhadap Biaya, Mutu dan Waktu pada Proyek Konstruksi di Kota Denpasar - Dewi, I Gusti Ayu Wulan Krisna; Pramana, I Made Wahyu (Jurnal Talenta Sipil, 2025)
Change orders often occur in constructionprojects, particularly in building projects, involvingadditions, changes, or reductions of work items during the implementation process. These changes significantly affect the project’s cost, quality, and schedule. The negative impact of changeorders is frequently felt across these three aspects, as observed inconstruction projectsin Denpasar. Therefore, ananalysis isneeded to determine the extent ofthe negativeimpact caused by change orders. This study aims to measure the impact of change orders on cost, quality, and time in constructionprojects in Denpasar. The research process began with a literaturereview toidentify the variablesand indicators-related to change orders and theireffects on projectimplementation. Subsequently, questionnaires were prepared and distributed to projectmanagers, sitemanagers, and project leaders in Denpasar as respondents. The collected data was then analyzed using the Partial Least-Square (PLS) method to gain deeper insight into the impact of change orders. The findings reveal that change orders have a significantly negative impact on project performance. Specifically, the influence of changeorders onproject cost is recorded at 31.6%, on quality at 16.8%, and on time at 23.2%. These results highlight that change orders play a crucial role in determining theefficiency and effectiveness of building construction projects. Therefore, effective management of changeorders is essential to minimize their negative impact and ensure that projects are executed according to plan interms of cost, quality, and time..